2013
DOI: 10.1016/j.dld.2012.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Ocular symptoms are not predictive of ophthalmologic inflammation in inflammatory bowel disease

Abstract: Ocular symptoms are frequent in inflammatory bowel disease, but are non-specific and rarely associated with ocular inflammation. Systematic ocular symptoms assessment is of poor value for diagnosing ocular inflammation in inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Cloché et al[ 59 ] evaluated 74 of 305 IBD patients with ophthalmological symptoms. Only one patient presented with scleritis and they concluded that ocular symptoms were neither specific nor associated with ocular inflammation.…”
Section: Ocular Involvementmentioning
confidence: 99%
“…Cloché et al[ 59 ] evaluated 74 of 305 IBD patients with ophthalmological symptoms. Only one patient presented with scleritis and they concluded that ocular symptoms were neither specific nor associated with ocular inflammation.…”
Section: Ocular Involvementmentioning
confidence: 99%
“…Cloche at al. reported that low rate ocular inflammation may have a role ocular symptoms of IBD in a large cohort study (14). Önal at al.…”
Section: Discussionmentioning
confidence: 95%
“…Posterior scleritis has also been described associated with choroidal infiltrates and retinal detachment [15]. However, Cloché et al [4] reported that up to 30% of the IBD patients showed posterior segment complications.…”
Section: Posterior Segment Complicationsmentioning
confidence: 99%
“…The prevalence of dry eye has been reported in up to 40% of IBD patients [4,19]. The etiology of the high prevalence of dry eye symptoms in this population is unclear.…”
Section: Treatment-related Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation